Plasma Zinc Difference in Children with Thalassemia β Major Received Deferiprone or Deferasirox Zinc - Kusumawardhani, Wahyu; Salimo, Harsono; Riza, Muhamad (Indonesian Journal of Medicine, 2020)
Background: Thalassemia is a blood disease characterized by the most frequently found autosomal recessive hereditary hemolytic anemia. It requires repeated blood transfusions for life. Routine blood transfusion can cause complications in the form of accumulation of ferritin in the tissue. Iron chelation therapy is considered effective for treating body iron deposits. However, iron chelation therapy has the side effect of decreasing levels of other important minerals such as zinc (Zn). This study aimed to examine plasma zinc difference in children with Thalassemia β major received deferiprone or deferasirox zinc.Subjects and Method: This was a cross sectional study conducted at Dr. Moewardi Hospital, Surakarta, from February to April 2017. A sample of 40 children with thalassemia β major aged 3 to 18 years who received deferiprone iron chelation and deferasirox at least 6 months was selected by consecutive sampling. The dependent variable was serum zinc levels. The independent variables were iron deferiprone and deferasirox. Plasma zinc levels were measured by atomic absorption spectroscope. The data were analyzed by t test.Results: Zinc levels in patients with deferiprone therapy (Mean= 54.50; SD= 11.02) were lower than deferasirox therapy (Mean= 60.95; SD= 20.71), but statistically not significant (p= 0.229).Conclusion:Zinc levels in patients with deferiprone therapy are lower than deferasirox therapy, but not statistically significant.Keywords: zinc, deferiprone, deferasirox, children with thalassemia β majorCorrespondence: Wahyu Kusumawardhani. Department of Pediatrics, Faculty of Medicine, Universitas Sebelas Maret/ Dr. Moewardi Hospital, Surakarta, Central Java. Phone/ Fax: 0271-633348. Email: dhanisuryadiraja@gmail.comIndonesian Journal of Medicine (2020), 05(02): 102-108https://doi.org/10.26911/theijmed.2020.05.02.02